TED to fight tedious classes. TED-based activities for practical English classes - Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The e-book contains sample exercises based on TED recordings which can be used during practical English classes (and not only). The e-book is divided into four thematic parts: Language and communication, The animal world, Medical issues and Psychology and well-being. There are five chapters in each part, all based on a different recording.
Keywords: TED; język angielski - nauczanie; edutainment; autonomia; Practical English classes; autonomy